Some Considerations on Creativity Support for VR Audio - Camci, Anil (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2019)
As the consumer interest in VR grows, the community of content creators working in this domain expands accordingly. Given the intrinsic role of audio in VR experiences, this growth necessitates authoring tools for immersive audio that can cater to a wide range of designers regardless of their expertise in spatial audio. In this article, we discuss some of the modern considerations on designing interactive tools for creativity support in VR audio. We provide examples from existing spatial audio design software, and discuss areas in which new tools can facilitate, for expert and novice users alike, the use of immersive audio in compelling new VR experiences.